Allied Health Professional Support in Pediatric Inflammatory Bowel Disease: A Survey from the Canadian Children Inflammatory Bowel Disease Network—A Joint Partnership of CIHR and the CH.I.L.D. Foundation - Wael El-Matary; Eric I. Benchimol; David Mack; Hien Q. Huynh; Jeff Critch; Anthony Otley; Colette Deslandres; Kevan Jacobson; Jennifer deBruyn; Matthew W. Carroll; Eytan Wine; Johan Van Limbergen; et al. (Canadian Journal of Gastroenterology and Hepatology)
Objectives. The current number of healthcare providers (HCP) caring for children with inflammatory bowel disease (IBD) across Canadian tertiary-care centres is underinvestigated. The aim of this survey was to assess the number of healthcare providers (HCP) in ambulatory pediatric IBD care across Canadian tertiary-care centres. Methods. Using a self-administered questionnaire, we examined available resources in academic pediatric centres within the Canadian Children IBD Network. The survey evaluated the number of HCP providing ambulatory care for children with IBD. Results. All 12 tertiary pediatric gastroenterology centres participating in the network responded. Median full-time equivalent (FTE) of allied health professionals providing IBD care at each site was 1.0 (interquartile range (IQR) 0.6–1.0) nurse, 0.5 (IQR 0.2–0.8) dietitian, 0.3 (IQR 0.2–0.8) social worker, and 0.1 (IQR 0.02–0.3) clinical psychologists. The ratio of IBD patients to IBD physicians was 114 : 1 (range 31 : 1–537 : 1), patients to nurses/physician assistants 324 : 1 (range 150 : 1–900 : 1), dieticians 670 : 1 (range 250 : 1–4500 : 1), social workers 1558 : 1 (range 250 : 1–16000 : 1), and clinical psychologists 2910 : 1 (range 626 : 1–3200 : 1). Conclusions. There was a wide variation in HCP support among Canadian centres. Future work will examine variation in care including patients’ outcomes and satisfaction across Canadian centres.